Management of Patients With Hepatitis C Virus, Monoclonal Gammopathy of Undetermined Significance, and Multiple Myeloma - Alisse Hannaford BS; David Del Bello MD; Siyang Leng MD; Ajai Chari MD, PhD; Ponni Perumalswami MD; Douglas Dieterich MD; Andrea Branch PhD (SAGE Publishing, 2017)
Background and Aim: The vast majority of the 2.7 million individuals in the United States who are currently infected with hepatitis C virus (HCV) were born between 1945 and 1965. The median age of these patients in this particular generation at the time of this writing was 55 years. In the general population, older age is a risk factor for multiple myeloma (MM) and other monogammopathies. As the baby boomer population ages, HCV providers are increasingly likely to encounter HCV-infected patients with a monoclonal gammopathy. Guidelines for managing these patients are needed. Methods: We conducted a detailed case series investigation of 4 HCV-positive patients with MM or a monoclonal gammopathy disorder. Patients were followed at the Mount Sinai Faculty Practice liver clinic. We also performed a detailed review of the literature exploring if there is any known association between HCV, MM, and monoclonal gammopathy. Results and Conclusions: There is no convincing evidence of a causal association between HCV and MM. HCV is linked to type II and type III cryoglobulinemia, specific kinds of monoclonal gammopathies of determinable significance. Whether a link exists between HCV and MM or monoclonal gammopathy of undetermined significance is unclear. Our case series provides the first evidence that modern HCV treatments with direct-acting antivirals can be safely and effectively co-administered with MM chemotherapy.